Grade 4 Pneumonitis in a Patient Treated with a Combination of Gemcitabine and Docetaxel for Recurrent Leiomyosarcoma of the Uterus - Connor Wang; Stephen Rose; Lori Mankowski Gettle; Ryan Spencer (Hindawi Limited, 2020)
Gemcitabine and docetaxel combination chemotherapy is the standard of care for patients with unresectable recurrent or metastatic leiomyosarcoma of the uterus. Although they are generally well-tolerated agents, they can also cause severe and life-threatening pulmonary toxicities. Here, we describe a case of grade 4 pneumonitis due to gemcitabine and docetaxel in a 74-year-old woman with recurrent, metastatic uterine leiomyosarcoma. Despite early recognition of chemotherapy-induced lung injury and early administration of corticosteroid, she developed noncardiogenic pulmonary edema, diffuse alveolar hemorrhage, and acute respiratory distress syndrome. She required multiple intubations and a tracheostomy. Physicians should not only be aware of gemcitabine and docetaxel's potential to cause life-threatening pulmonary injuries but also recognize the variability in clinical presentations and treatment responses, the radiographic findings of these lung toxicities, and the need for early corticosteroid therapy in these cases.